Active Retrograde Extra Backup with a Mother-and-Child Catheter to Facilitate Retrograde Microcatheter Collateral Channel Tracking in Recanalization of Coronary Chronic Total Occlusion - Yong Wang; Xiao-Jiao Zhang; Hong-Wei Zhao; Cheng-Fu Wang; De-Feng Luo; Qing-Kun Meng; Yu Zhu; Jie Tao; Bao-Jun Chen; Yi Li; Ai-Jie Hou; Bo Luan (Journal of Interventional Cardiology)
Objective. To explore the feasibility and safety of the active retrograde backup (ARB) for treatment of chronic total occlusion (CTO) during retrograde percutaneous coronary intervention (PCI). Background. Guiding support plays an important role in guidewire and microcatheter coronary channel (CC) tracking in retrograde PCI therapy for patients with CTO. However, the feasibility and safety of retrograde active use of a mother-and-child catheter are still unclear. Patients and Methods. A total of 271 consecutive patients with CTO who underwent retrograde PCI between January 2015 and January 2020 were retrospectively analyzed. Clinical data of two groups were compared to evaluate the feasibility and safety of ARB. Results. Of the 271 patients, 69.0% (187/271) underwent therapy through the septal branch, 31.0% (84/271) through the epicardial collateral channel, and 47.6% (129/271) through active retrograde extra backup with a mother-and-child catheter to facilitate retrograde microcatheter collateral CC tracking. The time of wire CC tracking was shorter in the ARB group than that in the non-ARB group (25.4 ± 8.5 vs 26.4 ± 9.7, p=0.348), but there was no significant difference. The duration of the retrograde microcatheter tracking (10.2 ± 3.8 vs 15.5 ± 6.8, p=0.012) and the retrograde approach (62.8 ± 20.3 vs 70.4 ± 24.3, p=0.026) in the ARB group was significantly shorter than that in the non-ARB group. The radiation dose (223.6 ± 112.7 vs. 295.2 ± 129.3, p=0.028), fluoroscopy time (50.6 ± 21.3 vs 62.3 ± 32.1, p=0.030), and contrast volume (301.8 ± 146.7 vs 352.2 ± 179.5, p=0.032) in the ARB group were significantly lower than that in the non-ARB group. There were no life-threatening procedural complications in either group. Complications unrelated to ARB included two cases of donor-vessel dissection, one case of CC perforation, and two cases of target-vessel perforation. There was no statistically significant difference in major adverse cardiac and cerebrovascular events between the groups during hospitalization p>0.05. Conclusion. ARB is feasible, safe, and conducive to guidewire and microcatheter CC tracking in the recanalization of coronary CTO. It improves procedural efficiency and is worthy of further promotion.